Radiation therapy for benign lymphoepithelial cysts of parotid glands in HIV patients. (26th March 2013) - Mourad, Waleed F.; Hu, Kenneth S.; Shourbaji, Rania A.; Lin, Wilson; Harrison, Louis B.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To report the long‐term outcomes of radiation therapy (RT), and the impact of fractionation size and RT duration on HIV patients with Benign Lymphoepithelial Cysts (BLEC) of the parotid glands. Methods From January 2000 to 2011, 30 patients were eligible for our single institution retrospective study. Both parotids were treated with 24Gy via RT. The median age at RT, HIV diagnosis, and duration of HIV seropositive was 45 years (28–64), 38 years (23–53), and 11 years (6–35), respectively. Patients were stratified into two groups. Group A and B received 2Gyx12 and 1.5Gyx16, respectively. Results After a median follow‐up of 66 months (12–141), the overall response (OvR) was 93% of the patients. Specifically, complete response (CR) and partial response (PR) were 80% and 13%, respectively. In group A, 100% had CR. Treatment failure was 7% and all were in group B, which was mainly due to poor compliance. A Chi‐square test showed significant relationship between OvR and RT duration (P <0.001), and a positive trend between CR and fraction size of 2Gy (P = 0.053). All acute toxicities were grade ≤2, specifically mucositis (48%), xerostomia (45%), skin erythema (41%), and altered taste (14%). Two patients (6.7%) experienced long‐term grade 1 xerostomia. Conclusion RT provides a sustained long‐term cosmetic control for BLEC of the parotid glands in HIV patients. Failures are uncommon, and the late side effects have been negligible.